2018
DOI: 10.1590/abd1806-4841.20188396
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis from Do-It-Yourself slime

Abstract: Do-It-Yourself slime (DIY slime) is a current fad among kids and teenagers. Making this homemade goop is as much fun as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
“…15 More recently, several case reports have been published reporting contact dermatitis to homemade "slime." [16][17][18][19][20][21] Slime is a popular plaything made at home with combinations of borax, household detergents, bleach, glue, shaving cream, and colorings/dyes. 20 In 2017, borax-containing slime "recipes" were reported to cause second-and third-degree burns.…”
Section: Resultsmentioning
confidence: 99%
“…The mainstay of therapy of contact dermatitis caused by slime or Play-Doh is avoidance of these substances. The addition of oral antihistamines (cetirizine and loratadine typically) and topical corticosteroid creams (triamcinolone and mometasone) is often employed to relieve persistent cases [10,11]. The usage of topical corticosteroids should be restricted to the smallest amount necessary to resolve the rash, especially in children.…”
Section: Discussionmentioning
confidence: 99%